Effects of Inrush Current on the Hysteresis Loop and Load Influences on the Transient Current of a Single-Phase Transformer - Yahiou, A.; Mellah, H.; Bayadi, A.; Abid, M. (Engineering, Technology & Applied Science Research, 2022)
When putting any unloaded transformer into service, a high-value current that can be very dangerous, called the inrush current, appears. The latter may cause problems and consequences in the electrical system. The challenges of visualizing the effects of transient regimes on the iron core’s characteristics and the influence of the type of load on inrush current characteristics are covered in this study. The main purpose of this paper is to treat the influence of this transient phenomenon on the hysteresis loop of a single-phase transformer, in terms of its size, area, or position, and therefore, the influence of the load on the transient regime. A general study of the electromagnetic characteristics of the transformer iron core will be presented. Then, using the ATP-EMTP program, the purpose of the realized simulations is to visualize the relationship between the hysteresis loop and the magnetizing inrush current in the transient state. The results show the decrease of the hysteresis loop area and their shift with respect to the origin of the axes following the increase in the transient inrush current peak. As the second part of this article, there is a study of the influence of the load on the transient regime, i.e. inrush current. This is accomplished by adding a load with different configurations and various connections. The purpose is to find the effect of the load on the reduction of the transient inrush current phenomenon.